Taste in Art—Exposure to Histological Stains Shapes Abstract Art Preferences. (October 2017) - Böthig, Antonia M.; Hayn-Leichsenring, Gregor U.
Exposure to art increases the appreciation of artworks. Here, we showed that this effect is domain independent. After viewing images of histological stains in a lecture, ratings increased for restricted subsets of abstract art images. In contrast, a lecture on art history generally enhanced ratings for all art images presented, while a lecture on town history without any visual stimuli did not increase the ratings. Therefore, we found a domain-independent exposure effect of images of histological stains to particular abstract paintings. This finding suggests that the 'taste' for abstract art is altered by visual impressions that are presented outside of an artistic context.